Human ITCH E3 Ubiquitin Ligase Deficiency Causes Syndromic Multisystem Autoimmune Disease - Lohr, Naomi J. (Elsevier, 2010)
Ubiquitin ligases play an important role in the regulation of the immune system. Absence of Itch E3 ubiquitin ligase in mice has been shown to cause severe autoimmune disease. Using autozygosity mapping in a large Amish kindred, we identified a linkage region on chromosome 20 and selected candidate genes for screening. We describe, in ten patients, identification of a mutation resulting in truncation of ITCH. These patients represent the first reported human phenotype associated with ITCH deficiency. These patients not only have multisystem autoimmune disease but also display morphologic and developmental abnormalities. This disorder underscores the importance of ITCH ubiquitin ligase in many cellular processes.